Modal analysis for engine crankshaft - Mohamad Saufi, Mohamad Zainury (2008)
Crankshaft is a fundamental and a very crucial part in internal combustion engine. Its role as the main translational-rotational converter have been used and perfected as early as 1226 by Al-Jazari in his water pump machines. This paper consists of finding the mode shape and natural frequency of a 3 cylinder 4 stroke engine crankshaft. The test is done in both simulation and also experimental using a simple test rig. The crankshaft is modeled using Solidworks computer aided design (CAD) software and simulation analysis is done in ALGOR computational aided engineering (CAE) software. Experimental is done by using impact hammer to excite the crankshaft and data recorded using data acquisition system (DAS) connected to sensor located on the crankshaft. The post processing software used after experimental is done is Me’ScopeVES software. The results for both simulation and experimental is compared. The mode shapes is simulated using ALGOR. The differences in the results between simulation and experimental is discussed. The final selected natural frequency for simulation is based on mesh aspect ratio of 80%. Simulation natural frequency in 1st mode is 688.494 Hz (bending), 2nd mode is 707.661 Hz (bending), 3rd mode is 1098.9 Hz (bending), 4th mode is 1273.63 Hz (torsion) and 5th mode is 1664.23 Hz (bending). Meanwhile, the experimental natural frequency (x-axis) in 1st mode is 668 Hz, 2nd mode is 722 Hz, 3rd mode is 1300 Hz, 4th mode is 1480 Hz and 5th mode is 1580 Hz. Experimental natural frequency (y-axis) in 1st mode is 724 Hz, 2nd mode is 742 Hz, 3rd mode is 850 Hz, 4th mode is 1130 Hz and 5th mode is 1300 Hz. Experimental natural frequency (z-axis) in 1st mode is 475 Hz, 2nd mode is 724 Hz, 3rd mode is 775 Hz, 4th mode is 1120 Hz and 5th mode is 1320 Hz. The discrepancy errors recorded between simulation and experimental is ranging from 2 – 23.11%.